Management of corneal melting in a patient with long-standing rheumatoid arthritis – case report - Mimier, Małgorzata; Janczak, Dawid; Hill-Bator, Aneta; Sebastian, Agata; Wiland, Grażyna; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Corneal melting is a rare ocular complication of rheumatoid arthritis, associated with poor prognosis. Rapid course of the disease and unpredicted treatment response, which depends on a patient general state and disease severity, make every case a challenge and requires a cooperation between ophthalmologists and rheumatologists. We present a case of a 58-year-old woman with corneal melting, who was successfully treated with systemic corticosteroids and methotrexate, along with ocular surgery.